2013
DOI: 10.1080/15685551.2013.771308
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a new series of rigid polytriazole resins

Abstract: A novel series of polytriazole resins were synthesized by using aromatic diazides and N,N,N′,N′-tetrapropargyl-p,p′-diaminodiphenylmethane (TPDDM) as raw materials. The chemical structures of the resins were characterized by Fourier transform infrared spectroscopy (FTIR) and nuclear magnetic resonance. Rheological behavior indicates that the resins can be processed in a low-temperature region, and some of them have good solubilities in common organic solvents. Differential scanning calorimetry and FTIR results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…Huang group [16][17][18][19][20][21][22][23][24][25] has prepared a series of thermosetting polytriazole resins by 1, 3-dipolar cycloaddition reaction of azides and alkynes since 2002. The study results have shown that the polytriazole resins are cured at low temperature (60~80°C) and the cured resins have good thermal properties and mechanical properties, and the resins have been used as matrices in advanced composites.…”
Section: Introductionmentioning
confidence: 99%
“…Huang group [16][17][18][19][20][21][22][23][24][25] has prepared a series of thermosetting polytriazole resins by 1, 3-dipolar cycloaddition reaction of azides and alkynes since 2002. The study results have shown that the polytriazole resins are cured at low temperature (60~80°C) and the cured resins have good thermal properties and mechanical properties, and the resins have been used as matrices in advanced composites.…”
Section: Introductionmentioning
confidence: 99%
“…Since the copper (I)‐catalyzed azide‐alkyne cycloaddition (CuAAC) “click reaction” was introduced by Sharpless and Meldal independently, it has become a useful tool for connecting polymer fragments to form linear, star, and dendrimer architectures, because of its high efficiency, regioselectivity and mild reaction conditions. Polymers constructed using regular triazole linkages through click polymerization of small diynes and bisazides, called polytriazoles, are very brittle and show poor processability . To improve the polymer properties, researchers have inserted polyols, such as PEG and PDMS into the structure to obtain polytriazole elastomers.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The classical (thermal) 1,3-dipolar cycloaddition can be performed between azides and terminal alkynes as well as internal triple bonds. Generally, the reactivity of alkynes for the click reaction is rather low due to its high electron density at the alkyne functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of metal‐free click‐polymerization procedures is of high interest. In the recent years, a significant effort has been devoted to the development of metal‐free click reactions . The classical (thermal) 1,3‐dipolar cycloaddition can be performed between azides and terminal alkynes as well as internal triple bonds.…”
Section: Introductionmentioning
confidence: 99%